FIQH PEREMPUAN KEKINIAN DAN KEINDONESIAAN - Mukhlis Mukhtar (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2019)
Women's fiqh comes from the naqli and aqli arguments, so in essence women's fikhi in the sense of understanding the existence of women is the result of ijtihad (ijtihādȋ fiqh). Therefore, female fikhi in the present era is certainly different from the classical fikhi of women. Likewise, women's fiction in Arab countries is certainly different from women's fikh in Indonesia. In the present era women fikhi provide equal opportunities proportional to the types of women and men to obtain rights and obligations that are balanced (fair) in their lives.